Slondok Dryer Application Utilizes Waste Energy from Steaming Cassava - Dimas Riki Romadhon; Nofa Ardana; An'nisa Sholihah; Bagiyo Condro Purnomo; Saifudin Saifudin; Suroto Munahar (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2023)
Magelang Regency has several superior products for MSMEs, one of which is the production of processed boilers / slondok. The partner in the creativity program for students in the application of science and technology (PKM-PI) is UMKM Slondok Pak Narto with the address Druju Tegal Hamlet, Plosogede Village, Ngluwar District, Magelang Regency, Central Java. The problem faced by partners is that it requires a large area to dry product raw materials, besides that during the rainy season the drying process cannot be carried out so slondok production will stop. The purpose of this PKM-PI is to apply appropriate technology in the form of an oven that utilizes heat from the exhaust waste gas from combustion in the boiler steamer furnace and slondok fryer. This heating oven is able to help dry the raw materials of the product up to 45%.